2008
DOI: 10.1002/aic.11498
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of liquid distribution over structured packing

Abstract: in Wiley InterScience (www.interscience.wiley.com).The thickness of a liquid film on the structured packing inside a distillation column was measured at the region of counter-current flow of gas and liquid by fiber-optic sensors. The local distribution of liquid inside a typical geometrical cell formed by the corrugated Koch 1Y sheets was examined in this study. It is shown that, in the vicinity of the sheet contact points inside the cell, the liquid film thickness is maximal, and peculiar meniscuses are forme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 17 publications
(15 reference statements)
3
16
0
Order By: Relevance
“…Actually, at the macroscale, the capillary pressure translates the local curvilinear gas–liquid interface dynamic. The effect of capillary dispersion is, therefore, consistent with Alekseenko et al experiments that showed the presence of a meniscus at the sheet's contact points. They also showed that, at this very spot, the liquid is redistributed over the corrugated surface.…”
Section: Mathematical Modelsupporting
confidence: 89%
See 1 more Smart Citation
“…Actually, at the macroscale, the capillary pressure translates the local curvilinear gas–liquid interface dynamic. The effect of capillary dispersion is, therefore, consistent with Alekseenko et al experiments that showed the presence of a meniscus at the sheet's contact points. They also showed that, at this very spot, the liquid is redistributed over the corrugated surface.…”
Section: Mathematical Modelsupporting
confidence: 89%
“…These phases are not (except perhaps at very low saturation) completely independent, since adjacent sheets are in contact and the wetting liquid can flow from one sheet to the other. This latter point is confirmed in the experimental study done by Alekseenko et al who measured by fiber‐optic sensors the thickness of the liquid film in the space confined by two adjacent corrugated sheets. They have shown that, in the vicinity of the contact points between corrugated sheets, menisci form is at the origin of local liquid flow redistribution over the corrugated surfaces.…”
Section: Introductionsupporting
confidence: 65%
“…The main limitation of this method is possible hysteresis during the contact between the needle and the film surface. However, this method was retained (i) because the rear side of the reactor was made of stainless steel, and so techniques based on light absorption or capacitance (or resistance) were inapplicable [24][25][26][27][28], and (ii) because the technique had to be mobile to measure the film thickness over the entire tilted surface; techniques requiring highly accurate alignments, such as optical fibers [29][30][31] or fluorescent techniques [25,32,33] were therefore difficult to apply. For each condition, 15 measurements were made over the whole tilted surface to analyze film evenness.…”
Section: Hydrodynamics and Gas-liquid Mass Transfer 321 Liquid Filmentioning
confidence: 99%
“…However, studying the effects of different dumped and structured packing types, column internals and distributor designs on liquid distribution, spreading and emerging flow patterns requires time-consuming measurements and, thus, provides only time-averaged data that do not take flow dynamics and local flow patterns into account. To counterbalance the low temporal and spatial resolution such collector devices are often complemented by fast optical and electrical probes installed at few selected locations [13,14]. But the permissible number of such probes is rather small with respect to the possible spatial flow variations and also such instruments are invasive and, therefore, may have a considerable impact on the flow.…”
Section: Liquid Distribution Measurement Techniquesmentioning
confidence: 99%